Optical Interconnect Waveguide in Electronic Circuit - Siti Sarah Binti Md Sallah; Sawal Hamid Md Ali; Nurjuliana Binti Juhari; P. Sushitha Menon; Md Shabiul Islam (International Journal of Electrical and Computer Engineering (IJECE), 2016)
The increasing demand in silicon nano-photonics has encouraged many researchers to put more efforts to explore the feasibility of using optics in the communication medium in order to replace the conventional electrical interconnects (EIs). In this paper, we proposed a SOI- based waveguide in the optical interconnect (OI) link at an operating frequency of 1550nm to work as an interconnection path in a circuit. The performance capability of the OI link was tested using a two-stage CE amplifier to work as the interconnection path from the 1st stage to the 2nd stage amplifier. In term of optical performances, the optical waveguide interconnect managed to achieve a single mode condition for a TE mode and fulfill the receiver sensitivity of a photodiode. While, in term of electrical performance, a two-stage CE amplifier is able to produce a high gain, a wide bandwidth and high slew rate. The proposed implementation of the OIs waveguide is succesfully enhance the performance of the two-stage CE amplifier as well as the analog electronic circuit applications.